Can science fix climate change? : a case against climate engineering. - Hulme, Mike (Polity Press, 2014)
Climate change seems to be an insurmountable problem. Political solutions have so far had little impact. Some scientists are now advocating the so-called ‘Plan B’, a more direct way of reducing the rate of future warming by reflecting more sunlight back to space, creating a thermostat in the sky.